COVID-19 Stigmatization: Concept Analysis - Sinem Dağ; Günay Hazir; Gülten Güvenç; Emine İyigün (Galenos Publishing House, 2021)
The new coronavirus disease (COVID-19) is spreading rapidly worldwide and has been declared as a pandemic in 2020. Countries have taken many measures against the pandemic. However, the spread of the virus could not be entirely slowed down. People who are diagnosed with COVID-19 and their families, healthcare workers, citizens of countries in the Far East, the elderly, and people who travel are stigmatized. Stigmatization can have a negative effect on individuals, families, and on society. Discrimination as a result of stigma prevents people in society from receiving proper care and treatment and leads to psychological problems. Stigma should be prevented to mitigate the effects of COVID-19. The objective of this study was to analyze the concept of COVID-19 stigma. This concept was analyzed with the Walker and Avant concept analysis method. In literature review, articles that are accessible and relevant for concept analysis were found by searching with the keywords "damgalamak, damga, etiketleme, stigma, stigmatize, stigmatization, kavram analizi, concept analysis, COVID-19, COVID-19 stigma, and COVID-19 damgalama" in PubMed, Science Direct and Google Academic databases between the months of January and May, 2020. However, no study was found about COVID-19 stigma concept analysis in literature. Therefore, this COVID-19 stigma concept analysis will provide guidance to healthcare professionals.